Efeitos da ozonioterapia no tratamento da artrite reumatoide - Saraiva, Leonardo (2020)
Rheumatoid arthritis (RA) is an inflammatory, autoimmune, chronic disease and is considered the most common joint disease in humans. This process leads to the destruction of joints and, consequently, a substantial reduction in quality of life. There are countless treatments for this disease, however, ozone therapy is still little explored. The objective of this dissertation was to verify the effects of Ozonotherapy in the treatment of RA. To answer the objectives, two systematic reviews were carried out, the first entitled "Treatment of Rheumatoid Arthritis With Ozone Therapy: Systematic Review" and the second production was entitled "Ozone Therapy in the Treatment of Rheumatoid Arthritis: Systematic Review with Meta Analysis of Experimental Studies". The search strategy was composed of descriptors indexed to the DeCS: “Ozone Therapy” AND “Arthitis Rheumatoids”. Results of the first production: 77 studies were selected, and only 01 (one) study met the inclusion criteria, in this systematic review it can be said that the use of ozone therapy was effective in the treatment of RA, in addition, there was still an improvement in the state individuals, such as decreased pain and improved functional capacity. In the second production, the statistical heterogeneity between the studies was assessed by the inconsistency test (I2). A value of p <0.05 was considered statistically significant. All analyzes were conducted using the Rev-Man 5.4 software (Cochran Collaboration). The main outcome analyzed was the reduction of synovial TNF-α (tumor necrosis factor alpha). Results: in all, 233 studies were found in the 09 scientific databases, but only 05 studies met the inclusion criteria and 03 studies constituted the meta-analysis. The ozone groups 40 μg / mL and 50 μg / mL versus oxygen, obtained 95% CI respectively - 1.44 [-2.39, -0.50] and -1.44 [-2.38, -0.50], as well as the total sum of the ozone vs oxygen groups 95% CI - 1.08 [-1.73, -0.43], which also demonstrated an excellent consistency between studies (I2 = 0%). For comparisons between studies with RA induction, the ozone groups at concentrations of 40 μg / mL and 50 μg / mL obtained 95% CI -1.75 [-2.54, -0.96] and -1.81 [-2 respectively , 83, -0.80] and in the total sum of the groups, ozone obtained 95% CI -1.46 [-2.05, -087]. The consistency between the 3 included studies was I2 = 0%. This systematic review and meta-analysis suggests that treatment using ozone therapy in the treatment of RA in rats was effective and doses from 20 μg / mL to 50 μg / mL, show better efficacy results and lower levels of TNF-α when compared to rats who received other types of interventions. It can be concluded that a systematic review complements the other, since the first brings results in humans and the second in animals. Thus, these results contribute for clinical research to be carried out in the area of Human Aging.